Teacher's Method in Learning the Qur'an - Laras Nurhalifah; Rhadiatul Rahmi; Vini Aprilia Putri; Nurhasnah Nurhasnah; Latifah Hanum (International Journal of Multidisciplinary Research of Higher Education, 2022)
This study aims to analyze the methods used by teachers in learning the Qur'an. This study used a qualitative method with a case study type, the data source was taken from forty-two informants through in-depth interviews who were selected using purposive sampling and observation techniques. All results of interviews and observations were analyzed thematically with Miles and Huberman's qualitative data analysis. The research findings show that there are nine methods used by teachers in teaching the Qur'an including; i) Iqra', ii) Tartil, iii) Baghdadiyah, iv) Tahsin v) Recitations, vi) Lamma, vii) As-Sahl, viii) Talaqqi, ix) Peer tutor. The results of this study can be used as initial data for future researchers in examining different issues related to this problem and various other issues that are relevant to this context.